The relationship between alcohol abuse and attachment styles among undergraduate students studying psychology at the University of Limpopo, South Africa - Debang, Selaelo (My University, 2023)
Background: Literature suggests that alcohol abuse is widespread among university students globally, including in South Africa. While extensive research indicates the impact of socio-economic factors on alcohol abuse, there is lack of research to show the impact of interpersonal attachments on alcohol abuse. Previous research has indicated that attachment styles can predict problematic alcohol use; however, few studies have examined this relationship among university students. Therefore, the principal objective of this study was to explore the relationship between alcohol abuse and attachment styles among undergraduate psychology students at the University of Limpopo, thus filling this gap. Methods: A quantitative cross-sectional study was undertaken to explore the potential relationship between alcohol abuse and attachment styles among students. A convenience sample of 272 students completed self-report measures of alcohol (the Alcohol Use Disorders Identification Test) and attachment (the Experience in Close Relationships-Revised). Descriptive statistics, Spearman correlation rank test, and Mann-Whitney U test analyses were conducted. Results: A statistical analysis of the findings of the study showed that anxious attachment was significantly and positively correlated to higher alcohol use levels (p = 0.006), whereas avoidant attachment was significantly and negatively correlated to higher alcohol use levels. Furthermore, the findings of the study revealed that male students reported higher rates of alcohol use, and thus expressed both anxiousattachment and avoidant attachment than female students. Conclusion: This study recommended that future research should use longitudinal designs to offer extensive insights into the relationship between alcohol abuse and attachment styles.
Thesis (M.A. (Psychology)) -- University of Limpopo, 2023
Keywords: Alcohol; Attachment; Students; Alcohol abuse; Anxious attachment; Avoidant attachment; Alcoholism; College students -- South Africa -- Limpopo; Alcoholism -- Psychological aspects; Attachment behavior